Konflik Sosial Dalam Cerpen Berjudul “Barang Bekas” Karya Padli Aditya Pratama (Teori Konflik Lewis A. Coser): Penelitian - Nindy Dian Carmelita (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This study analyzes the short story "Barang Bekas" by Padli Aditya Pratama through the lens of Lewis A. Coser's Theory of Social Conflict (1956), which serves as the dominant analytical tool to dissect interpersonal and social conflicts in a rural Indonesian setting. The narrative explores the friendship between Icha and Salimah, which deteriorates due to familial prejudice and social inequality, mirroring real-world dynamics in village education systems. Employing a qualitative literary approach, the research examines how conflicts function both destructively causing fragmentation and constructively fostering resilience and social change. Findings reveal that such conflicts, rooted in power imbalances and cultural norms, highlight educational implications, including the potential use of literature to promote tolerance and inclusion in rural schools. This analysis underscores the theory's effectiveness as a scalpel for uncovering deeper social structures, offering recommendations for pedagogical applications in addressing discrimination. The study contributes to sociology and education by bridging literary analysis with practical social insights.